Air Restrictor and Turbocharger Influence for the Formula Student Engine Performance. (2017) - Melaika, Mindaugas; Rimkus, Alfredas; Vipartas, Tadas
Abstract: Paper presents the investigation of Formula Student car engine performance when different air inlet restrictors are applied. AVL BOOST numerical simulation model is created according to real engine parameters. The research includes simulation of restrictor diameters, which varied from 60 mm to 15 mm. The smaller intake manifold pipe diameter influenced engine performance – increased air intake hydraulic resistance and worsened cylinder volumetric efficiency that resulted in lower engine power and higher brake specific fuel consumption. In order to compensate the power loss, turbocharging system was simulated for the selected engine. Simulation results revealed that turbocharger improved engine performance.